Combined etching technology for controlling surface damage precursors to improve laser damage resistance of fused silica - Zhigang Yuan; Wenhui Deng; Qiancai Wei; Bo Li; Lian Zhou; Qinghua Zhang; Jian Wang; Xiaotao Zu; Xiangyang Lei; Bo Zhong (Results in Physics)
At present, a single post-processing technology will always introduce secondary defects (trace pollution elements and structural defects) while removing surface processing defects of fused silica components, which limits the further improvement of the laser damage threshold of the components. Therefore, to effectively remove surface defects in optically-processed fused silica and suppress defect regeneration is the key to improve the laser damage resistance performance of the components. Based on the complementarity of anisotropic ion beam etching and isotropic HF acid etching, a combined etching technology is proposed for fused silica components used in engineering. The combined etching can remove most of the fragmented defects on fused silica surface to achieve relatively good surface quality with a root mean square roughness of 0.666 nm. After the combined etching, the contents of most impurity elements decrease by approximately an order of magnitude. Besides, the contents of the structural defects significantly reduce. Therefore, The zero probability damage threshold and the 100 % probability damage threshold increase by 32.41 % and 57.46 %, respectively. The results show that the combined etching technology can effectively improve the laser damage resistance performance of fused silica components, especially under high fluence laser irradiation, which is very important for the high power output and stable operation of laser facilities.